GDBC: A tool for generating global-scale distributed basin morphometry. (September 2016) - Shen, Xinyi; Vergara, Humberto J.; Nikolopoulos, Efthymios I.; Anagnostou, Emmanouil N.; Hong, Yang; Hao, Zengchao; Zhang, Ke; Mao, Kebiao
Abstract: In response to the vital role of geomorphological analysis in natural hazards study, geomorphology, distributed hydrology and other related disciplines, we present the first global basin morphometric product of 30 characteristics, 9 archived elementary including stream order, stream number, stream length, basin relief, basin length, basin perimeter, maximal flow length, down valley length and overland flow length, and 21 derivable from these elementary morphometric characteristics. Characteristics of basins discharging to every grid-cell of the global earth surface are generated at 30 arcsec resolution from the remotely sensed HydroSHEDS dataset. This product does not exist in previous literature because tree-structural grid-cells bring large computational redundancy to basin delineation and thus computing basin characteristics. To generate this product within a reasonable timeframe, we introduce in this paper an efficient framework to reduce the algorithm complexity to linear, O( N ). We have presented a few geomorphologic findings using the generated product. Highlights: An efficient framework of O(N) complexity to calculate distributed basin characteristics. 29 commonly used geomorphologic variables are included. The first distributed global product at 30 arcsec spatial resolution.